Improving the Speaking Skill by Vlog as Learning Media for Teaching Long Functional Text for Eighth Grade Students at SMPN 17 Medan - Khairunnisa br. Batubara; Christine Helena Natali (Randwick International of Education and Linguistics Science Journal, 2020)
This research was aimed to develop Video Blog as media of speaking in teaching long functional text for eighth grade students at SMPN 17 Medan. This research applied Research and Development (R&D) model proposed by Gall, Gall and Borg (2003) through six procedures: gathering data and information, conducting need analysis, designing, expert validating, revising, and producing final product. The subjects of this research were 30 students of eighth grade of SMPN 17 Medan. The instruments of collecting data were the teacher’s lesson plan, teacher’s interview and students’ questionnaires result. The data were analyzed by using descriptive analysis. The product has been validated by two experts. The assessment from the first expert was 4,5 or 91,3% while the assessment from the second expert was 4,6 or 93%. Based on the experts’ judgment result, the research showed that: The Video Blogs were eligible and valid as learning media in teaching and learning speaking long functional text for eighth grade students at SMPN 17 Medan. Furthermore, the video blogs give many benefits for students, such as to improve their speaking, make them enjoy and easier to speak long functional text. It means that the vlog media development was appropriate for the eighth grade students of SMPN 17 Medan.